The Contribution of Dietary Factors to Dental Caries and Disparities in Caries - Mobley, Connie (2009)
Frequent consumption of simple carbohydrates, primarily in the form of dietary sugars is significantly associated with increased dental caries risk. Malnutrition (under or over nutrition) in children is often a consequence of inappropriate infant and childhood feeding practices and dietary behaviors associated with limited access to fresh, nutrient dense foods substituting instead, high-energy low cost and nutrient poor sugary and fatty foods. Lack of availability of quality food stores in rural and poor neighborhoods, food insecurity, and changing dietary beliefs resulting from acculturation including changes in traditional ethnic eating behaviors, can further deter healthful eating and increase risk for Early Childhood Caries and obesity. America is witnessing substantial increases in children and ethnic minorities living in poverty, widening the gap in oral health disparities noted in the Surgeon General's Report, Oral Health in America. Dental and other care providers can educate and counsel pregnant women, parents and families to promote healthy eating behaviors and should advocate for governmental policies and programs that decrease parental financial and educational barriers to achieving healthy diets. For families living in poverty, however, greater efforts are needed to facilitate access to affordable healthy foods, particularly in urban and rural neighborhoods in order to effect positive changes in children's diets and advance the oral components of general health.